Analisis Yuridis Perjanjian Pranikah Ditinjau dari Undang-Undang Nomor 1 Tahun 1974 di Kota Pematang Siantar: Legal Analysis of Prenuptial Agreements Reviewed from Law Number 1 of 1974 in Pematang Siantar City - Vindi Verdiana; M. Hendra Pratama Ginting (Jurnal Hukum Bisnis, 2026)
A prenuptial agreement is a legal instrument that regulates the management of assets and the division of responsibilities between husband and wife in a marriage. This research is motivated by the low level of understanding and implementation of prenuptial agreements in Pematang Siantar City, despite being regulated in Article 29 of Law Number 1 of 1974 concerning Marriage. The purpose of this research is to analyze the implementation of prenuptial agreements from a legal perspective, assess their effectiveness in practice, and identify factors that hinder their implementation in society. This research uses a normative legal method, namely, research based on primary legal materials by examining theories, concepts, legal principles, and relevant laws and regulations. The results show that the majority of the community does not understand the function, procedures, and benefits of prenuptial agreements. The main obstacles identified include a lack of legal socialization, psychological factors, the influence of conservative cultural and religious values, and the community's economic limitations. Although prenuptial agreements are legally binding if made in accordance with legal provisions, in practice, they have not yet become part of community customs. Based on these findings, low public understanding, cultural and economic factors, and minimal outreach from relevant institutions are the main obstacles to the implementation of prenuptial agreements. Therefore, this study recommends improving legal education through collaboration between state institutions, legal practitioners, and community leaders to expand public access and understanding of legal rights in marriage.